150 questions to a guerrilla - Bayo, Alberto (Pickle Partners Publishing, 2015)
General Alberto Bayo is possibly the one individual most responsible for Fidel Castro's military successes against the Batista regime. Find the answers to such questions as: What is the most efficient size of a guerrilla unit? How will new volunteers be trained? What should be done if the enemy fire on us by surprise?